Small Protein B upregulates sensor kinase bvgS expression in Aeromonas veronii - Liu, Zhu; Liu, Peng; Liu, Shuanshuan; Song, Haichao; Tang, Hongqian; Hu, Xinwen (Frontiers in Microbiology, 2015)
Earlier studies reveal that Small Protein B (SmpB), a class of well-conserved tmRNA-binding proteins, is essential for the trans-translation process, which functions as a system for translation surveillance and ribosome rescue. Here, we report a previously unrecognized mechanism by which SmpB alone positively regulates the expression of a sensor kinase, BvgS, in Aeromonas veronii. A reporter plasmid was constructed in which the promoter of bvgS was used to control the expression of the enhanced green fluorescent protein (eGFP) gene. When the reporter plasmid was co-transformed with a SmpB expression construct into E. coli, the relative fluorescence intensity increased about 3-fold. Transformation with a truncated form of smpB gene showed that the C-terminus had little effect, while N-terminus unexpectedly increased eGFP production. Next, a series of SmpB mutants were generated by site-directed mutagenesis. When the mutants SmpB (G11S) or SmpB (E32AG) was used in the experiment, eGFP expression dropped significantly compared with that of wild type SmpB. Further，purified SmpB was shown to bind the promoter regions of bvgS in the agarose gel retardation assay. Quantitative RT-PCR analysis showed that eGFP transcript levels increased approximately 25-fold in the presence of SmpB. Likewise, bvgS transcripts decreased significantly in smpB knockout A. veronii. Similar to BvgS inhibition, smpB knockout in A. veronii displayed a reduced capability in salt tolerance. Collectively, the data presented here will facilitate a deeper understanding of SmpB-mediated regulatory circuits as a transcriptional factor in A. veronii.